Third World protest between home and the world - Rao, Rahul, 1978- (Oxford : Oxford University Press, 2010)
Journeying through the writings of James Joyce, Rabindranath Tagore, Edward Said, and Frantz Fanon, Rao demonstrates that important currents of Third World protest have long battled against both the international and the domestic, in a manner that combines nationalist and cosmopolitan sensibilities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International relations; Cosmopolitanism; Nationalism